PERANCANGAN APLIKASI JALUR PENDAKIAN DAN MONITORING PENDAKI GUNUNG UNGARAN BERBASIS GLOBAL POSITIONING SYSTEM (GPS) - Khoirur Rozikin; Nuris Dwi Setiawan (Teknik: Jurnal Ilmu Teknik dan Informatika, 2021)
Ungaran Mountain has a height of 2050 meters above sea level, this mountain is suitable for beginner climbers who want to know more about climbing hobbies, Ungaran climbers themselves only take about 3-5 hours, depending on the speed of walking, the climbing route is also quite light and very suitable for heating before starting to climb higher mountains. Thus many novice climbers who want to try to climb and conquer Mount Ungaran, armed with minimal experience of mountain climbing, the risks they face are even greater, ranging from getting lost, being hypothermic to death while climbing. To make it easier for Ungaran mountain climbers who are dominated by novice climbers in this study, the Ungaran Mountaineering Track and Monitoring Application Based on the Global Positioning System (GPS) on the Android System "which was built to make it easier for Ungaran mountain climbers to access information provided by Ungaran mountain climbers. needed to climb Mount Ungaran, and it is also useful for the team at base camp to monitor climbers who climb..